Takhrij and Syarah Hadith of Agrotechnology Black Cumin Plant Studies in Medicine - Lisda Rahmawati Haque; Wahyudin Darmalaksana; Anna Aina Roosda (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with regard to black cumin. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study is that black cumin has been used in the world of medicine in the Middle East as well as in the era of ancient Egypt, considering that black cumin has many benefits that contain various elements for treatment. The conclusion of this study is that the takhrij and syarah hadiths about black cumin with agrotechnological analysis have many benefits and opportunities to reveal the various benefits contained in black cumin.